2002
DOI: 10.1002/tcr.10019
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of HOx Radicals in the Marine Boundary Layer: Testing the Current Tropospheric Chemistry Mechanism

Abstract: OH and HO(2) radicals, atmospheric detergents, and the reservoir thereof, play central roles in tropospheric chemistry. In spite of their importance, we had no choice but to trust their concentrations predicted by modeling studies based on known chemical processes. However, recent direct measurements of these radicals have enabled us to test and revise our knowledge of the processes by comparing the predicted and observed values of the radical concentrations. We developed a laser-induced fluorescence (LIF) ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Unexpectedly high HO 2 concentrations and increasing ratios of observed to modeled HO 2 , and thus P(O 3 ) HO2 , at greater NO have been observed in the free troposphere [ Folkins et al , 1997; Faloona et al , 2000]. There is some evidence for this effect at Okinawa Island [ Kanaya and Akimoto , 2002]. Although the authors of this study state that the HO 2 dependence is quantitatively reproduced by the model, above 1 ppbv of NO a plot of their HO 2 observations and model calculations [ Kanaya and Akimoto , 2002, Figure 4] shows that observed HO 2 does not decrease to the expected extent, with mixing ratios more than 10 times larger than expected for 2.5 × 10 −6 s −1 < J(O 1 D) < 7.5 × 10 −6 s −1 at ∼10 ppbv NO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly high HO 2 concentrations and increasing ratios of observed to modeled HO 2 , and thus P(O 3 ) HO2 , at greater NO have been observed in the free troposphere [ Folkins et al , 1997; Faloona et al , 2000]. There is some evidence for this effect at Okinawa Island [ Kanaya and Akimoto , 2002]. Although the authors of this study state that the HO 2 dependence is quantitatively reproduced by the model, above 1 ppbv of NO a plot of their HO 2 observations and model calculations [ Kanaya and Akimoto , 2002, Figure 4] shows that observed HO 2 does not decrease to the expected extent, with mixing ratios more than 10 times larger than expected for 2.5 × 10 −6 s −1 < J(O 1 D) < 7.5 × 10 −6 s −1 at ∼10 ppbv NO.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence for this effect at Okinawa Island [ Kanaya and Akimoto , 2002]. Although the authors of this study state that the HO 2 dependence is quantitatively reproduced by the model, above 1 ppbv of NO a plot of their HO 2 observations and model calculations [ Kanaya and Akimoto , 2002, Figure 4] shows that observed HO 2 does not decrease to the expected extent, with mixing ratios more than 10 times larger than expected for 2.5 × 10 −6 s −1 < J(O 1 D) < 7.5 × 10 −6 s −1 at ∼10 ppbv NO. We have now observed unexpectedly high HO 2 at high NO in the metropolitan environment in Nashville.…”
Section: Resultsmentioning
confidence: 99%
“…Although they may not lead to an immediate clarification of processes, the accumulation of these comparisons at multiple sites is important for the identification of common tendencies. For example, HO 2 concentrations are overestimated in clean coastal regions (Sommariva et al, 2004;Kanaya et al, 2002Kanaya et al, , 2007a, and this assists systematic surveying of the processes responsible for the discrepancies. Recent observations revealed that OH concentrations under high volatile organic compound (VOC) and low NO x conditions were systematically larger than the modeled concentrations.…”
Section: Introductionmentioning
confidence: 98%
“…Although they may not lead to an immediate clarification of processes, the accumulation of these comparisons at multiple sites is important for the identification of common tendencies. For example, HO 2 concentrations are overestimated in clean coastal regions (Sommariva et al, 2004;Kanaya et al, 2002Kanaya et al, , 2007a, and this assists systematic surveying of the processes responsible for the discrepancies. Recent observations revealed that OH concentrations under high volatile organic compound (VOC) and low NO x conditions were systematically larger than the modeled concentrations.…”
Section: Introductionmentioning
confidence: 99%